2020
DOI: 10.1111/wvn.12420
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Connections Groups: A Pilot Test of an Intervention Aimed at Enhancing Resilience Among Nurse Leader Mothers

Abstract: Background Nurse leaders who are mothers are at significant risk for experiencing stress, burnout, and occupational fatigue. Authentic Connections (AC) Groups is an intervention shown to be effective for fostering resilience among at‐risk moms, including physicians; however, it has not previously been tested with nurse leaders. Aims Our aims were to test the feasibility and acceptability of the AC Groups intervention with nurse leader mothers and examine its effects on participant resilience, as measured by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Various researchers have signified certain fundamental factors that foster resilience among nurses. Chesak et al (2020) and Ramalisa et al (2018) concluded that resilience can be attributed to a caring workplace and collegial support networks for nurses which are crucial in building employees' morale, fostering cohesion, and sharing accountabilities amongst them. A resilience training program can increase the capacity to mitigate workplace adversity, increase personal resilience, and influence their decision to remain in the workforce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various researchers have signified certain fundamental factors that foster resilience among nurses. Chesak et al (2020) and Ramalisa et al (2018) concluded that resilience can be attributed to a caring workplace and collegial support networks for nurses which are crucial in building employees' morale, fostering cohesion, and sharing accountabilities amongst them. A resilience training program can increase the capacity to mitigate workplace adversity, increase personal resilience, and influence their decision to remain in the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…This finding means as FLMNs' supportive and empowering leadership practices increase, so do nurses' resilience and job involvement. Nurse leaders play a pivotal role in building and sustaining a safe and healthy work environment (Chesak et al, 2020). Nurses who have a caring nurse manager have more opportunities to engage in decision-making, improve communication, and develop resilient behaviors, thus resulting in a higher level of job involvement.…”
Section: ± 068mentioning
confidence: 99%
See 1 more Smart Citation
“…Two randomized trials were conducted, with providers at the Mayo Clinics in Arizona and Minnesota respectively. Findings showed improvements compared to controls on multiple indicators of well-being (including cortisol levels) with moderate effect sizes, and gains sustained well after the program was completed (for summaries, see Chesak et al, 2020; Luthar et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…To support resilience, institutions must provide multiple avenues for workers to exchange feelings safely and manage stress and negative emotions effectively. Many existing peer-support programs (from before the pandemic) and structured stress management interventions have been shown to be beneficial to decrease stress, promote resilience, 9 and support an organizational culture of shared responsibility for well-being. At the outbreak of the pandemic, it quickly became apparent at Mayo Clinic that there was a need to support employee well-being and a broad desire by staff to provide support to fellow employees.…”
Section: Peer Support and Stress Managementmentioning
confidence: 99%